The World Anti-Doping Code in sport: Update for 2015 - Hughes, David (Aust Prescr, 2015)
Some athletes cheat by using drugs or medical methods such as transfusion to enhance their performance. However, this may put their health at risk. The World Anti-Doping Agency prohibits certain methods and drugs that may enhance performance, harm the athlete or violate the spirit of sport. Some may be banned only during competitions, but others are banned at all times. Prohibited substances include over-the-counter and prescription medicines. It is therefore important for athletes and health professionals to check what is permitted. There are many resources available through organisations such as the Australian Sports Anti-Doping Authority and the World Anti-Doping Agency.